IGF-1 deletion affects renal sympathetic nerve activity, left ventricular dysfunction, and renal function in DOCA-salt hypertensive mice - Xiao, Bing; Liu, Fan; Lu, Jing-Chao; Chen, Fei; Pei, Wei-Na; Yang, Xiu-Chun (Physiological research, 2019)
To determine the influence of IGF-1 deletion on renal sympathetic nerve activity (RSNA), left ventricular dysfunction, and renal function in deoxycorticosterone acetate (DOCA)-salt hypertensive mice. The DOCA-salt hypertensive mice models were constructed and the experiment was classified into WT (Wild-type mice) +sham, LID (Liver-specific IGF-1 deficient mice) + sham, WT + DOCA, and LID+ DOCA groups. Enzyme-linked immunosorbent assay (ELISA) was used to detect the serum IGF-1 levels in mice. The plasma norepinephrine (NE), urine protein, urea nitrogen and creatinine, as well as RSNA were measured. Echocardiography was performed to assess left ventricular dysfunction, and HE staining to observe the pathological changes in renal tissue of mice. DOCA-salt induction time-dependently increased the systolic blood pressure (SBP) of mice, especially in DOCA-salt LID mice. Besides, the serum IGF-1 levels in WT mice were decreased after DOCA-salt induction. In addition, the plasma NE concentration and NE spillover, urinary protein, urea nitrogen, creatinine and RSNA were remarkably elevated with severe left ventricular dysfunction, but the creatinine clearance was reduced in DOCA-salt mice, and these similar changes were obvious in DOCA-salt mice with IGF-1 deletion. Moreover, the DOCA-salt mice had tubular ectasia, glomerular fibrosis, interstitial cell infiltration, and increased arterial wall thickness, and the DOCA-salt LID mice were more serious in those aspects. Deletion of IGF-1 may lead to enhanced RSNA in DOCA-salt hypertensive mice, thereby further aggravating left ventricular dysfunction and renal damage.
Keywords: Hypertension; Insulin-Like Growth Factor I; ledviny; sympatická vlákna postgangliová; Kidney; Desoxycorticosterone Acetate; zvířata; insulinu podobný růstový faktor I; myši; Norepinephrine; myši inbrední C57BL; Mineralocorticoids; Mice; myši knockoutované; mineralokortikoidy; deoxykortikosteron-21-acetát; Male; Mice, Knockout; hypertenze; Sympathetic Fibers, Postganglionic; dysfunkce levé srdeční komory; Mice, Inbred C57BL; Ventricular Dysfunction, Left; noradrenalin; Animals; mužské pohlaví